Oncological relevance of proximal gastrectomy in advanced gastric cancer of upper third of the stomach - Yoshiro Imai; Ryo Tanaka; Kentaro Matsuo; Mitsuhiro Asakuma; Sang-Woong Lee (Surgery Open Science, 2024)
Background: The oncological relevance of proximal gastrectomy in advanced gastric cancer remains unclear. We aimed to examine the frequency of lymph node metastasis in advanced gastric cancer to determine the oncological validity of proximal gastrectomy selection. Materials and methods: This study included consecutive 71 patients with locally advanced gastric cancer in the upper third of the stomach who underwent total gastrectomy at our institution between 2001 and 2017. Lymph node metastasis and its therapeutic value index were examined to identify candidates for proximal gastrectomy. Metastatic and 3-year overall survival rates of numbers 3a and 3b lymph nodes were examined from 2010 to 2019. Results: The metastatic rate and therapeutic value index of numbers 4d, 5, 6, and 12a lymph nodes were zero or low. The number 3 lymph node had a metastatic rate and therapeutic value index of 36.6 % and 31.1, respectively. The metastatic and 3-year overall survival rates of the number 3a lymph node were 32.7 % and 89 %, respectively, whereas those of the number 3b lymph node were 3.8 % and 100 %, respectively. All patients with positive metastasis to the number 3b lymph node received adjuvant chemotherapy. Histopathological findings of positive metastasis to the number 3b lymph node were located in the lesser curvature, and the tumor diameter exceeded 40 mm. Conclusion: For advanced gastric cancer of the upper third of the stomach, the indications of localization to the lesser curvature and a tumor diameter of >40 mm should be considered cautiously.